2018
DOI: 10.1038/s41526-018-0057-9
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 and the dysregulation of immune, bone, muscle, and metabolic homeostasis during spaceflight

Abstract: We have previously reported that exercise-related secretion of IL-6 by peripheral blood mononuclear cells is proportionate to body weight, suggesting that IL-6 is gravisensitive and that suboptimal production of this key cytokine may contribute to homeostatic dysregulations that occur during spaceflight. This review details what is known about the role of this key cytokine in innate and adaptive immunity, hematopoiesis, and in bone, muscle and metabolic homeostasis on Earth and in the microgravity of space and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 108 publications
1
24
1
Order By: Relevance
“…Indeed, it has been very well appreciated that ionizing radiation exposure will cause both pro-inflammatory and anti-inflammatory expression as cellular signals attempt to resolve the unique normal tissue radiation injury that occurs both acutely and longer-term [80][81][82]. This immune signaling dysregulation has also been reported to occur when exposed to space radiation [83,84].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been very well appreciated that ionizing radiation exposure will cause both pro-inflammatory and anti-inflammatory expression as cellular signals attempt to resolve the unique normal tissue radiation injury that occurs both acutely and longer-term [80][81][82]. This immune signaling dysregulation has also been reported to occur when exposed to space radiation [83,84].…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of IL-6 and IL-8 is critical for the host because of high biological significance. Indeed, IL-6 plays a critical role in regulation of hematopoiesis, inflammation and immunity [49]. It is also correlated with the differentiation of B cells and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The function of the immune system is strongly impacted (Frippiat et al, 2016;Smith, 2018) with several studies reporting dysregulation or immunosuppression following simulated or real microgravity conditions (Boonyaratanakornkit et al, 2005;Crucian et al, 2015;Martinez et al, 2015;Thiel et al, 2017). Peripheral monocytes collected from astronauts post shortduration Space missions (13-16 days) showed that there was no change in the numbers of circulating monocytes indicating that the change to an immunosuppressive phenotype was not due a reduced cell number (Crucian et al, 2011).…”
Section: Microgravity-induced Cytoskeletal Regulation Of Immune and Cmentioning
confidence: 99%